2009
DOI: 10.4314/eamj.v86i4.46947
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity And Quality Of Life Among Head And Neck Cancer Patients Treated With Radical Radiotherapy

Abstract: Objectives:To determine the relative frequency of acute radiation morbidity and their perceived effect on quality of life among head and neck cancer patients treated with radical radiotherapy. Design: A cross-sectional study. Setting: Kenyatta National Hospital, Nairobi. Subjects: Thirty eight patients comprising 28 males and 10 females with ages ranging between 21 and 69 years were evaluated. Results: Most of the tumours occurred in the nasopharynx (38.6%). The rest of the tumours were equally divided between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A treatment regime that results in frequent and/or severe tissue reactions adversely affects compliance as more patients are likely to require prolonged rest days (6). In an earlier study it was found that patients attending radiotherapy for head and neck tumours at the KNH radiotherapy unit suffered frequent and severe radiation morbidity (23). This may explain, at least in part, the frequent and prolonged duration of treatment interruptions in this study.…”
Section: Discussionmentioning
confidence: 67%
“…A treatment regime that results in frequent and/or severe tissue reactions adversely affects compliance as more patients are likely to require prolonged rest days (6). In an earlier study it was found that patients attending radiotherapy for head and neck tumours at the KNH radiotherapy unit suffered frequent and severe radiation morbidity (23). This may explain, at least in part, the frequent and prolonged duration of treatment interruptions in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Among the 10 cases of 3(30%) patients received radiotherapy after surgery for locoregional treatment and all the patient developed several side effect of radiotherapy like dryness of mouth and throat, loss of taste sensation, pigmentation of skin and subcutaneous fibrosis during study period (table-XI). Another study reveals the same type of morbidity of acute radiation like difficulty in tasting food 76.3%, dryness of mouth 92% 25 and taste changes and dry mouth 26 .…”
Section: Discussionmentioning
confidence: 88%